Methods for removing heavy metals from water and wastewater: A review study - کیوان شایسته; Gity Behboody (Mashhad University of Medical Sciences, 2020)
Background and purpose: Heavy metals are one of the stable pollutants that do not decompose in nature and can import into the environment by sewage or wastewater of various industries. Usually, small quantities of these metals are required for the normal function of the body. But the excessive entrance of them into the body will cause poisoning. The purpose of this research is a review of various methods for the removal of heavy metals in the form of physical, chemical, and biological methods. Materials and Methods: In this paper, after searching related articles in the period 2014-2019 in databases such as Springer،Science direct، Scopus، Free paper, and John Wiley, presented references in this text were investigated to, obtain the latest finding on heavy metals removal methods. Results: Studies show that heavy metals can affect human health, so the removal of heavy metals is essential and various methods for the removal of heavy metals in the form of physical, chemical, and biological methods including membrane methods, chemical precipitation, electrochemical purification, ion exchange, adsorption, and bioremediation are used. Conclusion: The results of studies showed that heavy metals have destructive effects and it is necessary to remove and purify these metals from water and soil. The advantages and disadvantages of heavy metal removal methods make it easy to choose the right method in terms of cost and access to technical knowledge.